2022
DOI: 10.3389/fendo.2022.920470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Syndrome and Its Components on Clinical Severity and Long-Term Prognosis in Patients With Premature Myocardial Infarction

Abstract: BackgroundThe effects of metabolic syndrome (MS) on premature myocardial infarction (PMI) are not clear to date. This study aimed to investigate the impact of MS and its components on clinical severity and long-term prognosis in patients with PMI.MethodsWe enrolled 772 patients aged ≤45 years old who were diagnosed with acute myocardial infarction (AMI) at our hospital consecutively between 2015 and 2020. The patients were divided into an MS group and non-MS group. The parameters of clinical severity were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…MetS patients not only are at higher risk of developing myocardial infarction (MI) ( 122 ), but they also tend to have larger infarct size and more in-hospital complications ( 123 ). Of all the different components of MetS, hyperglicemia and BMI ≥28.0 kg/m 2 are associated with major adverse cardiovascular events (MACE) in patients with MI aged <45 year ( 124 ). Moreover, MetS in acute coronary syndrome (ACS) is significantly more present in women (55.9%-66.3%) than in men (40.2%-47.3%) ( 125 , 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…MetS patients not only are at higher risk of developing myocardial infarction (MI) ( 122 ), but they also tend to have larger infarct size and more in-hospital complications ( 123 ). Of all the different components of MetS, hyperglicemia and BMI ≥28.0 kg/m 2 are associated with major adverse cardiovascular events (MACE) in patients with MI aged <45 year ( 124 ). Moreover, MetS in acute coronary syndrome (ACS) is significantly more present in women (55.9%-66.3%) than in men (40.2%-47.3%) ( 125 , 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the literature, Obese patients with heart failure have lower concentrations of NT-proBNP due to increased expression of scavenger receptors and increased degradation of the peptides by adipose tissue [14]. It has previously been shown that people with HFpEF and normal NT-proBNP levels had a higher risk of death or rehospitalization from HF compared to people without HF [15]. Clinical studies have shown that patients with HFpEF and low levels of NT-proBNP responded better to mineralocorticoid receptor antagonists and angiotensin receptor blockers compared to patients with higher levels of NT-proBNP [16 -twenty].…”
Section: Discussionmentioning
confidence: 99%
“…1. Consequently, the meta-analysis included 10 observational studies [19][20][21][22][23][24][25][26][27][28].…”
Section: Study Retrievalmentioning
confidence: 99%
“…These studies were performed in Italy, Japan, Korea, Serbia, and China, and published between 2005 and 2022. As for study design, five studies were prospective cohort studies [21,23,25,27,28], four were retrospective cohort [20,22,24,26], and another one was post-hoc analysis of a clinical trial [19]. All the studies included patients with MI (total sample size: 33 197), with mean age of the patients varying from 41 to 71 years.…”
Section: Study Characteristicsmentioning
confidence: 99%